GENERATED WATER SULFATES OF KONCHEK MUD VOLCANO (KERCH PENINSULA) - NESTEROVSKYI, V.; DEIAK, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
New data about the water sulfates of the mud volcanoes in Kerch Peninsula have been represented. They are: gypsum, astrakhanite, epsomite, hexahydrite, pentahydrite. The morphological features and optical properties have been described. The genesis of these minerals has been proved.